Removing the Mystery in Supervision: Engaging in Transparent Supervision. Issue 1 (2nd January 2021) - Springer, Paul; Turns, Brie; Sibley, D. Scott; Eddy, Brandon
ABSTRACT: The supervisory relationship is one of the most important relationships in academic programs (Haug & Storm, 2014). Supervisors help provide direction, ethical guidance, and model adherence during supervision. Unfortunately, there are numerous challenges and issues that occur within supervision that cause tension and problems within the supervisory relationship (Todd & Storm, 2014). Not discussing diversity, models of therapy, or expectations in supervision can lead supervisees to enter a customer, complainer, or visitor relationship. This article introduces a new process for conducting supervision and enhancing the supervisory relationship. Transparent supervision aims to alleviate various challenges that arise in supervision by providing supervisors a framework for openly and transparently discussing topics in supervision.